Early Childhood Literacy Development Through The Baca Corner (Literacy Development at TK Tunas Rimba I Purwokerto) - Pujiati, Isti; Wachid Bambang Suharto, Abdul (International Proceedings of Nusantara Raya, 2022)
Reading corner is an alternative to developing literacy in early childhood institutions. When in the reading corner children are very excited and increase their great curiosity. This happens because the reading corner can improve children's ability to develop literacy. This study aims to describe through a reading corner can develop children's literacy skills. This research method uses a congruent embedded that applies one stage of descriptive qualitative data collection at a time. The results of this study found that the development of early childhood literacy can be stimulated through a reading corner that can be a reference for every class in early childhood education institutions. Some results show that the advantages of children who are often in the reading corner include: increasing children's imagination power in playing projects; the increasing vocabulary of each student; and children's social-emotional development getting better because of the interactions carried out in the reading corner.